A Systematic Review and Statistical Analysis of Prenatal Non-Invasive Diagnosis of Sickle Cell Disease [27O]. (May 2017) - Beebeejaun, Yusuf; Short, Lauren; Oteng-Ntim, Eugene
Abstract : INTRODUCTION: With over 2 million American affected by Sickle Cell Disease (SCD) and an estimated 17, 000 women affected by the disease in the United Kingdom, pregnancies complicated by SCD can be very challenging with various maternal and fetal complications. Currently, for SCD to be tested prenatally, fetal DNA is extracted by amniocentesis, chorionic villus sampling or cordocentesis and then analyzed by polymerase chain reaction (PCR). However, these procedures increase the risk of fetal miscarriage by up to 1%. In this presentation, we explore the efficacy of testing for SCD, non-invasively, using cell-free fetal DNA (cffDNA), which is extracted from maternal blood plasma. METHODS: Using literature databases we systematically reviewed existing studies pertaining to the use of cffDNA for non-invasive prenatal testing or diagnosis for SCD. The data collected as statistically analyzed, with the aim of appraising the sensitivity and specificity of this method of prenatal testing. RESULTS: Our analysis an average of 87.20% accuracy of diagnosis when using cffDNA to test for SCD, with 7.51% of fetuses incorrectly diagnosed. CONCLUSION: SCD is associated with significant maternal fetal complications such as intra uterine growth restrictions and preeclampsia. CffDNA for non-invasive prenatal SCD diagnosis appears to have the potential to be an accurate technique for the testing of this genetic disease. Whilst there are currently very limited data on the use of this technique for the specific testing of SCD, there is great opportunity for further research into the standardization and clinical application of this procedure.